2008
DOI: 10.1093/jxb/ern056
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of four members of the ACC synthase gene family in plum

Abstract: The regulation of ACC synthase (ACS) genes was studied in early (‘Early Golden’) and late (‘Shiro’) Japanese plum cultivars (Prunus salicina L.) in order to determine the role of this gene family in fruit ripening. Of the four Ps-ACS cDNAs isolated, two (Ps-ACS1 and -3) showed differential expression between the two cultivars. Ps-ACS1 accumulated during fruit ripening of ‘Early Golden’ (‘EG’) and ‘Shiro’ (‘SH’) in ethylene-dependent and -independent manners, respectively. Ps-ACS3a transcripts accumulated throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 54 publications
2
48
0
Order By: Relevance
“…Interestingly, a remarkable increase in the transcription of several ethylene-associated genes was eventually detected in plum during flower to fruit transition (i.e. in the same developmental stages used in the present study) [31, 67]. Genetic and biochemical analyses have shown that the five AtDELLA are actively involved in GA-signalling and they exhibit both overlapping and distinct roles in regulating GA-responsive growth [81, 8486].…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Interestingly, a remarkable increase in the transcription of several ethylene-associated genes was eventually detected in plum during flower to fruit transition (i.e. in the same developmental stages used in the present study) [31, 67]. Genetic and biochemical analyses have shown that the five AtDELLA are actively involved in GA-signalling and they exhibit both overlapping and distinct roles in regulating GA-responsive growth [81, 8486].…”
Section: Resultsmentioning
confidence: 80%
“…Previous studies have shown that the endogenous GA content readily increased along with the progression in fruit maturity and ripening [13, 15, 28]. These findings coupled with the stimulatory effect of exogenous GA in the fruit growth of several species suggested that GA is needed in mature fruiting tissues to allow fruit enlargement with potential involvement in ripening [1, 1213, 2931]. On the other hand, the scarcity of bioactive GA during plum fruit growth caused serious developmental disorders, including growth retardation, disturbed flower patterning and limited fruit characteristics [9].…”
Section: Introductionmentioning
confidence: 92%
“…Given the influence of NO on ethylene, it can be assumed that auxin effects were also modulated by NO. 74 Although cytokinins are involved in senescence programming, their relationship with NO via the ethylene signal transduction pathway in ripening research has not been documented. However, NO and cytokinin were found synergistically involved in betalaine accumulation 75 while cytokinins induced NO synthesis in cell cultures of parsley, tobacco and Arabidopsis.…”
Section: +mentioning
confidence: 99%
“…Ethylene can promote endogenous ethylene production via an auto-activating mechanism that regulates ethylene biosynthetic genes [35]. An increase in the transcript accumulation of LEACS2 induced by ethylene treatment can promote ethylene auto-activation and result in respiratory climacteric [11,31]. Exogenously applied ethylene has been found to induce autocatalytic ethylene production in petals of D. superbus var.…”
Section: Discussionmentioning
confidence: 99%